Role of extracellular ATP and P2 receptor signaling in regulating renal cyst growth and interstitial inflammation in polycystic kidney disease - Rangan, G (Frontiers in Physiology, 2013)
Polycystic kidney diseases (PKD) are a group of inherited ciliopathies in which the formation and growth of multiple cysts derived from the distal nephron and collecting duct leads to the disruption of normal kidney architecture, chronic interstitial inflammation/fibrosis and hypertension. Kidney failure is the most life-threatening complication of PKD, and is the consequence of cyst expansion, renal interstitial disease and loss of normal kidney tissue. Over the last decade, accumulating evidence suggests that the autocrine and paracrine effects of ATP (through its receptor family P2X and P2Y), could be detrimental for the progression of PKD. In vitro, ATP-P2 signaling promotes cystic epithelial cell proliferation, chloride-driven fluid secretion and apoptosis. Furthermore, dysfunction of the polycystin signal transduction pathways promotes the secretagogue activity of extracellular ATP by activating a calcium-activated chloride channel via purinergic receptors. Finally, ATP is a danger signal and could potentially contribute to interstitial inflammation associated with PKD. These data suggest that ATP-P2 signaling worsens the progression of cyst enlargement and interstitial inflammation in PKD.